This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
First , lets make a substitution to simplify the expression :
k = w − 2 1
The expression now becomes :
( w 2 − 4 1 ) 2 ( w 2 − 4 1 ) 2 + ( w − 2 1 ) 2 + ( w + 2 1 ) 2
Simplifying , we get :
( w 2 − 4 1 ) 2 ( w 2 + 4 3 ) 2
w 2 − 4 1 w 2 + 4 3 = 1 + ( w − 2 1 ) ( w + 2 1 ) 1 = 1 + k ( k + 1 ) 1
Now, it is simple telescoping and we get :
a n = n + 1 n ( n + 2 )
So, 6 a 5 = 3 5 .